Potential years of life lost to cancer in Mato Grosso, stratified by sex: 2000 to 2019 - Silvano Macedo Galvão; Marina Atanaka; Neuciani Ferreira da Silva Sousa; Noemi Dreyer Galvão (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2022)
ABSTRACT: Objective: To estimate the potential years of life lost (PYLL) to cancer in the State of Mato Grosso, from 2000 to 2019, stratified by sex, according to age groups and cancer types. Methods: It is a quantitative study with an ecological approach developed from secondary data, using the PYLL and its derivatives. Results: In the period analyzed, deaths from cancer in Mato Grosso resulted in 680,338 PYLL before the age of 80, with a variation of 82.5%. Of this total, 52.7% were assigned to males. The rate of the PYLL for cancer before the age of 60 was 70.9% in males, and 80.1% among women. The rates of PYLL increased in the period and showed slightly higher values in males. In the analysis according to age group, the rates of PYLL were also higher in males, except between the ages of 30 and 49. Lung cancers and lymphomas/leukemias resulted in greater losses of PYLL among men and female specific cancers (breast, cervical and uterine, and ovarian cancer) accounted for 36.26% of the PYLL among women, with variability per age groups. Conclusion: In Mato Grosso, the PYLL indicator for cancer presented unfavorable evolution between 2000 and 2019, with greater damage for males and for the younger population. Leukemias, lymphomas, and lung and breast cancers were the main causes for the PYLL.